Long-Term Outcomes of a Phase I Study With UV1, a Second Generation Telomerase Based Vaccine, in Patients With Advanced Non-Small Cell Lung Cancer - Brunsvig, Paal F.; Guren, Tormod Kyrre; Nyakas, Marta; Steinfeldt-Reisse, Claudius H.; Rasch, Wenche; Kyte, Jon Amund; Juul, Hedvig Vidarsdotter; Aamdal, Steinar; Gaudernack, Gustav; Inderberg, Else Marit (Frontiers in Immunology, 2020)
Human telomerase reverse transcriptase (hTERT) is a target antigen for cancer immunotherapy in patients with non-small cell lung cancer (NSCLC). We have tested a novel hTERT vaccine, UV1, designed to give high population coverage. UV1 is composed of three synthetic long peptides containing multiple epitopes identified by epitope spreading data from long-term survivors from previous hTERT vaccination trials. Eighteen non-HLA-typed patients with stage III/IV NSCLC with no evidence of progression after prior treatments, were enrolled in a phase I dose-escalation study of UV1 vaccination with GM-CSF as adjuvant, evaluating safety, immune response, and long term clinical outcome. Treatment with UV1 was well tolerated with no serious adverse events observed. Seventeen patients were evaluable for tumor response; 15 patients had stable disease as best response. The median progression free survival (PFS) was 10.7 months and the median overall survival (OS) was 28.2 months. The OS at 4 years was 39% (7/18). Five patients are alive (median survival 5.6 years) and none of these are known to have received checkpoint therapy after vaccination. UV1 induced specific T-cell responses in the majority (67%) of patients. Immune responses were dynamic and long lasting. Both immune response (IR) and OS were dose related. More patients in the highest UV1 dosage group (700 μg) developed IRs compared to the other groups and the IRs were stronger and occurred earlier. Patients in this group had a 4-year OS of 83%. The safety and clinical outcome data favour 700 μg as the preferred UV1 dose in this patient population. These results provide a rationale for further clinical studies in NSCLC with UV1 vaccination in combination with immune checkpoint blockade.